Nutritional Status and School Development in Children Aged 5 to 12 - Placencia López, Miladys; Edgardo Solórzano Solórzano, Sidar; Andrés Hernández Escobar, Arturo; Georgina Bravo Bonoso, Delia (International Journal of Psychosocial Rehabilitation, 2020)
Nutritional problems affect children’s health. Insufficient nutritional status in childhood increases the risk of death, inhibits cognitive development, and can affect lifelong health. This problem affects the poorest socioeconomic strata in society; in school age, this results in learning problems and high dropout rates. The objective of this research was to determine the nutritional status and its impact on the school development of children between 5 and 12 years of age. A descriptive and observational type study was conducted in a sample of 22 children who met the inclusion criteria. The research tools applied were surveys, interviews, and observation. The Body Mass Index was calculated as a measure of children’s nutrition status. The analysis found that nutritional status had a negative impact on children’s school years. Overweight and obesity affect approximately 70% of children. This result was related to the excessive consumption of sweets and frying. Demotivation, poor academic performance, and non-compliance with tasks are direct consequences of the negative feeding habits shown by students.